Transdermal Administration of Volatile Oil from Citrus aurantium-Rhizoma Atractylodis Macrocephalae Alleviates Constipation in Rats by Altering Host Metabolome and Intestinal Microbiota Composition. (18th January 2022) - Wang, Liangfeng; Wang, Fang; Zhang, Xiaofei; Chen, Qingyao; Xu, Jie; Li, Huiting; Li, FengQin; Yang, Ming
Abstract : Background . The Citrus aurantium - (ZhiShi, ZS-) Rhizoma Atractylodis Macrocephalae (BaiZhu, BZ) pairs are often found in herbal formulas for constipation. The volatile oils of ZS and BZ (ZBVO) have good pharmacological activity against constipation, but the mechanism for treatment of slow transit constipation (STC) remains unclear. Method . A rat model using diphenoxylate tablets was constructed to investigate if transdermal administration of ZBVO would mediate intestinal microorganisms and fecal metabolites and improve STC symptoms. The regulatory effects of ZBVO at 0.15, 0.30, and 0.60 mL kg -1 d -1 on STC rats were assessed by measuring fecal water content, intestinal propulsion rate, histopathology, expression of gastrointestinal hormones, brain and intestinal peptides, and inflammatory factors. The changes in intestinal flora of STC rats were analyzed by 16S rRNA gene sequencing. Moreover, the untargeted fecal metabolomics analysis was performed by ultraperformance liquid chromatography quadrupole time-of-flight mass spectrometer (UPLC-Q-TOF-MS) technology. Results . The results showed that ZBVO had a modulating effect on STC by increasing the fecal water content and intestinal propulsion rate. Transdermal administration of ZBVO decreased serum levels of interleukin 6 (IL-6) and tumor necrosis factor- α (TNF- α ) and increased the levels of gastrin (GAS) and substance P (SP). In addition, ZBVO increased 5-hydroxytryptamine (5-HT) levels and decreased vasoactive intestinal peptide (VIP) levels in colon and hippocampus tissues. The results of intestinal microbiota showed that ZBVO improved the diversity and abundance of intestinal microbiota and changed the community composition by decreasing Romboutsia and increasing Proteobacteria, Allobaculum, and Ruminococcaceae . And the feces metabolomics found that nicotinate and nicotinamide metabolism, purine metabolism, citrate cycle (TCA cycle), pyruvate metabolism, arachidonic acid metabolism, pyrimidine metabolism, and primary bile acid biosynthesis were modulated. Conclusion . These findings suggest that ZBVO can alleviate STC symptoms by promoting intestinal peristalsis, increasing fecal water content, regulating gastrointestinal hormone level, reducing the inflammatory response, and regulating brain and intestinal peptides after transdermal administration. And structural changes in the intestinal microbiota are closely related to host metabolism and intestinal microbiota destroyed in STC modeling could be significantly improved by the ZBVO, which provides a reference for the development of aromatic drug macrohealth products.